2005
DOI: 10.1179/174329305x36089
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural networks – an aid to welding induced ship plate distortion?

Abstract: A preliminary study on the potential application of artificial neural networks in welded structures was expanded to metal inert gas welding of steel plates of grades D and DH 36. The main controllable variables were plate thickness, steel grade, plate cutting process, and heat input. A series of welded plates of each grade was manufactured, covering plate thicknesses of 6 and 8 mm. The topography of each welded plate was evaluated after tacking the plates together and after welding, allowing the actual distort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Along with carbon these were largely unknown contributors to distortion, and the effects have been explained elsewhere [5,6]. The plate rolling treatment results showed that a normalised rolled process generated less subsequent distortion.…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…Along with carbon these were largely unknown contributors to distortion, and the effects have been explained elsewhere [5,6]. The plate rolling treatment results showed that a normalised rolled process generated less subsequent distortion.…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…Several investigators have used neural network models to predict properties and process variables. [64][65][66][67] In the function fit model by Babu et al, the free energy difference between ferrite and austenite was calculated as a function of composition and was related to FN. Vitek et al developed two neural net models, the first one, FNN-1998, to predict FN based on composition, and the second one, ORFN, to include the effects of cooling rate on the weld microstructure.…”
Section: Ferrite In Austenitic Stainless Steel Weldsmentioning
confidence: 99%
“…Artificial neural networks have been applied to analyse weld induced deformation in ship plate. 17 The prediction of weld bead geometry using ANNs has also been reported in the work of Vasudevan et al 18 Multilayer feed forward neural networks have been developed for modelling and online adjustment of welding parameters. 19 Fuzzy logic based techniques have also been used in the welding process.…”
Section: Introductionmentioning
confidence: 97%